Penggunaan Metode Storytelling dalam Pembelajaran sebagai Upaya Meningkatkan Keterampilan Berbicara Siswa - Mubarak, A. Faizul; Rozi, Fathor; Husin, Moh. (Institut Agama Islam Negeri (IAIN) Curup, 2022)
In an educational environment, mastery of speaking skills must be prioritized to achieve the expected targets according to applicable standards. At first glance, language mastery, especially students' speaking skills at the elementary school level, are not fully on target. This study aims to describe the use of the storytelling method as an alternative to improving Indonesian speaking skills, to foster appreciation for Indonesian literary works, and to find out the extent of the effect of the storytelling method in improving the speaking skills of class II MI Misbahul Fata students. This classroom action research uses the Kemmis and Mc spiral model design. Taggart which has four cycle components. Each research cycle includes stages; planning, observation and reflection. The subject of this study was students of class II MI Misbahul Fata, who in fact were in the Islamic boarding school environment, Klenang Kidul Village, Banyuanyar District, totaling 12 students. The problem that is rife with students is that they usually mix their mother tongue with the national language. There are several steps to implementing this storytelling method; The first is the opening stage, the second is the storytelling stage, the third is the closing and evaluation stage. In the early stages, the acquisition of student scores was 64.6% in the initial cycle from the previous data of approximately 59.5%, in the second cycle the average was 71.25%. In cycle I the completeness of the number of participants was around 58.3%, from cycle I it increased to 83.3% in cycle II. With these results, it can be concluded that the storytelling method can support students' speaking skills.